THE INFLUENCE OF INFLUENCER CREDIBILITY, VIDEO QUALITY, AND INFLUENCER ETHICS ON THE PURCHASE DECISIONS OF HALAL MSME PRODUCTS IN MEDAN CITY - Irhamsah Putra; Marliyah; Imsar (Jurnal Al-Iqtishad, 2026)
This study aims to analyze the influence of influencer credibility, video quality, and influencer ethics on the decision to purchase halal MSME products in Medan Sunggal District, Medan City. This study uses a quantitative approach with a survey method by distributing questionnaires to consumers who have seen promotions of halal MSME products through influencers. The sampling technique uses purposive sampling with 100 respondents. The data were analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with the help of the SPSS application. The results showed that, partially, influencer credibility did not have a significant effect on purchasing decisions, while video quality and influencer ethics had a positive and significant effect on purchasing decisions. The influencer ethics variable was the most dominant factor influencing purchasing decisions. Simultaneously, influencer credibility, video quality, and influencer ethics significantly affect purchasing decisions with an Adjusted R Square value of 0.555, which means that these three variables can explain 55.5% of the variation in purchasing decisions, while the rest is influenced by other variables outside this study. This study implies that in marketing halal MSME products, the aspects of ethics and digital content quality play a more important role than the personal credibility of influencers alone. Therefore, halal MSMEs need to pay attention to selecting ethical influencers and improving the quality of promotional content to encourage an increase in consumer purchasing decisions.